Milestone in predicting core plasma turbulence: successful multi-channel validation of the gyrokinetic code GENE - Klara Höfler; Tobias Görler; Tim Happel; Carsten Lechte; Pedro Molina; Michael Bergmann; Rachel Bielajew; Garrard D. Conway; Pierre David; Severin S. Denk; Rainer Fischer; Pascale Hennequin; et al. (Nature Communications)
Abstract On the basis of several recent breakthroughs in fusion research, many activities have been launched around the world to develop fusion power plants on the fastest possible time scale. In this context, high-fidelity simulations of the plasma behavior on large supercomputers provide one of the main pathways to accelerating progress by guiding crucial design decisions. When it comes to determining the energy confinement time of a magnetic confinement fusion device, which is a key quantity of interest, gyrokinetic turbulence simulations are considered the approach of choice – but the question, whether they are really able to reliably predict the plasma behavior is still open. The present study addresses this important issue by means of careful comparisons between state-of-the-art gyrokinetic turbulence simulations with the GENE code and experimental observations in the ASDEX Upgrade tokamak for an unprecedented number of simultaneous plasma observables.